"Caught in a Generation Gap": A Generation Perspective on Refugees Getting Old in Denmark—A Qualitative Study. (May 2018) - Nielsen, Dorthe S.; Minet, Lisbeth; Zeraig, Lina; Rasmussen, Dlama Nggida; Sodemann, Morten
Purpose: Older non-Western migrants in Europe are a vulnerable population, due to old age and multiple disadvantages related to language barriers and different understandings of care, health, and disease. Our aim was to gain a better understanding and insight into the care needs of families with refugee backgroundMethod: The study was designed as a qualitative exploration using semistructured individual interviews and family group interviews.Results: The results illustrate how vulnerability can "transmit" from one family member to another. Discrepancies between the older person's expectations and needs and society's expectations trap family members in ethical and moral dilemmas. This divides and stresses the family and results in difficult decision making, increased stress, and vulnerability.Conclusion and Implication: Migration and displacement can lead to ambivalent feelings among younger relatives regarding their role in caring for older relatives. Health professionals need to address and acknowledge this to be able to provide culturally congruent health care.